FAKTOR-FAKTOR YANG MEMPENGARUHI SKEPTISISME PROFESIONAL AUDITOR PADA KANTOR AKUNTAN PUBLIK - A’yun, Qurrotu; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe primary purpose of this research is to analyze the influence of audit situation, skill, independency, audit experience, and time budget pressure to the auditor professional skepticism. The respondent of this research is all the auditor staffs (partner, senior auditor and junior auditor) at Public Accountant Firm (PAF) Surabaya. The analysis technique has been carried out by using multiple linier regressions analysis. Based on the data analysis, it has been valid obtained on the validity test that all items in the research variable has been valid and it has been found on the reliability test that all variables are reliable. In the result of classic assumption test, it has been found that be regression models have met all classic assumptions i.e. all variable are normally distributed. Multicollinearity and heteroscedasticity does not occur. It has been found from the result of hypothesis test which has been done by using t test shows that audit situation and independency give positive influence to the auditor professional skepticism. Meanwhile, skills, audit experience, and time budget pressure do not give any influence to the auditor professional skepticism.Keywords: audit situation, independency, audit experience, time budget pressure, professional skeptiscism.